Application of Intraoral Scanners in Dental Health Guidance: Guidance Effectiveness - Akina, TANI; Kumiko, KAJI; Kazutoshi, KAKIMOTO; Akane, OMORI; Sizuo, HIGUCHI (The Japanese Journal of Conservative Dentistry, 2023)
Purpose: We have been studying the use of an intraoral scanner (IOS) in dental health guidance to quantify and visualize changes in periodontal tissues, to make it easier for patients to understand the state of periodontal tissues, and to improve the accuracy of examining the effects of treatment. In this study, the usefulness of dental health guidance using IOS was examined by comparing conventional dental health guidance methods and dental health guidance using IOS for faculty, staff, and students of the University who had not received dental health guidance. Subjects and Methods: The study subjects were a total of 9 faculty, staff, and students (mean age 41.6 years) who had never received adequate dental health guidance. Three dental hygienists provided the following dental health guidance at intervals of at least two weeks for each subject, in different order. (1) Conventional method 1: Dental health guidance without intraoral photographs, study models, or IOS records. (2) Conventional method 2: Dental health guidance using intraoral photographs and study models. (3) IOS method: Dental health guidance using IOS records (images showing changes in intraoral conditions and gingiva). In each dental health guidance, periodontal examination, plaque control record (PCR), and gingival condition were recorded on the survey form, and the oral cavity was scanned by IOS (TRIOS 3, 3Shape, Denmark). After the second recording, the subjects were asked to fill out a questionnaire about their discomfort during recording and the ease of understanding the instructions. IOS records were exported as 3D data in STL format and analyzed using 3D measurement data evaluation software. Results: The IOS recordings allowed for a more detailed examination of gingival changes than the conventional periodontal examination. The deviation of the marginal gingival surface obtained by aligning the IOS records had a poor relationship with the results of probing depth, gingival swelling and redness, and changes in BOP. No difference in guidance effectiveness was found between dental health guidance using IOS and conventional guidance methods. Conclusion: Currently, the clinical usefulness of dental health guidance using IOS is not high. Although the positional alignment of IOS records one tooth at a time can provide a very detailed examination of gingival changes, it is not clinically useful because it takes a very long time; block-by-block alignment is regarded as more appropriate. However, recording by IOS is a method that allows detailed gingival evaluation from a different viewpoint than conventional periodontal examination and is easy to understand for both the dental hygienist and the patient.